Analisis Pengaruh Shopping Liefe Style dan Fashion Involment terhadap Impulse Buying Behavior (Studi pada Konsumen Zara dan H&M di Sun Plaza Medan) - INDAH RIZKY ARYANTI (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2019)
The research was done at Zara and H&M customers in the famous shopping mall in Medan. The purpose of this research was to knew the influenced given by Shopping Life Style and Fashion Involment toward Impulse Buying Behavior in consumer buying activity. The type of research used was an associative with the study population that was consumers who visited in Sun Plaza Medan with an estimated 950 people per day except Saturday and Sunday. The sampling was a random sample with Slovin formula so that the number of samples was 91 respondents. Sources of research data that was primary data with data collection technique that was survey and observation. Data analysis techniques used multiple linear regression, classical assumption test and hypothesis test. Based on the results of research conducted, it could be submitted that partially and simultaneously Shopping life style and Fashion involment significantly influenced impulsing buying behavior study at ZARA and H & M consumers in Sun Plaza Medan. Shopping life style and Fashion involment have a very strong relationship toward impulsing buying behavior. Impulsing buying behavior could be explained by Shopping life style and Fashion involment equal to 80,6% and the other equal to 19,4% could be explained by other variable which not examined.